2018
DOI: 10.2139/ssrn.3248999
|View full text |Cite
|
Sign up to set email alerts
|

Five Things You Should Know about Cost Overrun

Abstract: This paper gives an overview of good and bad practice for understanding and curbing cost overrun in large capital investment projects, with a critique of Love and Ahiaga-Dagbui (2018) as point of departure. Good practice entails: (a) Consistent definition and measurement of overrun; in contrast to mixing inconsistent baselines, price levels, etc. (b) Data collection that includes all valid and reliable data; as opposed to including idiosyncratically sampled data, data with removed outliers, non-valid data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(88 citation statements)
references
References 55 publications
(36 reference statements)
0
87
0
1
Order By: Relevance
“…Lunn co-authored our first comment (Flyvbjerg et al, 2018) and would have been on the team for the present follow-up had he not died suddenly in February 2019. We missed him in preparing this note and will miss him going forward.…”
Section: One Error Covertly Corrected 13 Overtly Ignoredmentioning
confidence: 99%
See 3 more Smart Citations
“…Lunn co-authored our first comment (Flyvbjerg et al, 2018) and would have been on the team for the present follow-up had he not died suddenly in February 2019. We missed him in preparing this note and will miss him going forward.…”
Section: One Error Covertly Corrected 13 Overtly Ignoredmentioning
confidence: 99%
“…In a short forerunner to Flyvbjerg et al (2018), invited by the editor of Local Transport Today, 1 Flyvbjerg identified the above statement as a statistical error: https://doi.org/10.1016/j.tra.2019.06.011 ☆ We would like to dedicate this comment to the memory of our colleague Daniel Lunn, who was Professor of Statistics at the University of Oxford.…”
Section: One Error Covertly Corrected 13 Overtly Ignoredmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Extreme values, like those found here, are often erroneously seen as statistical outliers that are "a nuisance and must be removed" before analysis (Aguinis 2014: 3). Godfrey et al (2009) is an example of this approach, with more examples presented in Flyvbjerg et al (2018). But removal of extreme values is nearly always the wrong strategy.…”
Section: Gamesmentioning
confidence: 99%